Social pedagogues as members of multidisciplinary teams in a post-pandemic situation in Slovakia - Kristína Liberčanová (Sociální Pedagogika)
In light of the post-pandemic situation in education, adopting a transdisciplinary and multidisciplinary approach is vital. Social pedagogy encompasses a range of strategies and practices that can compensate, support, innovate, and provide services that align with the current needs of individuals, communities and the global challenges facing humanity. Social educators have become members of support teams, whether at the school level, educational and counseling institutions or local governments. These teams require multidisciplinary, interdepartmental or transnational collaboration. This paper presents the current post-pandemic situation in Slovakia and offers an overview of the latest development in social pedagogue education. Also, it describes the current process of standardising the social pedagogue profession and the functions of multidisciplinary teams in the school and counselling system.